Risorgimento and the free Italian churches now churches of the Brethren - Ronco, Daisy D.; International Brethren Conference on Mission June, 1996 Rome. (Bangor, Wales University of Wales, 1996)
Includes bibliographical references, maps, photographs, etc.
Written for the International Brethren Conference on Mission, Rome, June 1996.
Keywords: Brethren movement -- history -- Italy